2004
DOI: 10.2463/mrms.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of T1 Determination of Hyperpolarized 129Xe in Mouse Brain under Controlled-Flow

Abstract: The method of determining the longitudinal relaxation time of hyperpolarized 129Xe in the mouse brain has been established in vivo with the ventilation technique under controlled-flow conditions. The uptake and washout processes for nine mice were traced through observation of time-dependent changes in NMR (nuclear magnetic resonance) signal amplitudes and analyzed by means of a two-compartment model, thus providing the quantitative value of 14.1+/-1.6 s as the relaxation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…T 1i measured in rats have ranged widely from 3.6 to 26 s and T 1i in humans was reported as 8 s for white matter and 14 s for gray matter . In our own work, T 1i measured in mouse brain was reported as 14.1 ± 1.6 s (± standard deviation (SD; n = 9) .…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…T 1i measured in rats have ranged widely from 3.6 to 26 s and T 1i in humans was reported as 8 s for white matter and 14 s for gray matter . In our own work, T 1i measured in mouse brain was reported as 14.1 ± 1.6 s (± standard deviation (SD; n = 9) .…”
Section: Introductionmentioning
confidence: 61%
“…The origin of the peaks at around 198 ppm and 202 ppm are still unknown at present and needs to be determined in the future. To the authors' knowledge, the peak at around 210 ppm, which was identified as dissolved HP 129 Xe in the blood , has never been observed for mice .…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations